A novel high performance eutectic medium-entropy alloy with nanoprecipitates. (June 2022) - Xiao, Yake; Peng, Xianghe; Fu, Tao
Abstract: Eutectic medium-entropy alloys (EMEAs) have excellent plasticity but low strength. In this study, we designed and prepared a novel non-equiatomic Fe20 Cr20 Ni30 Al30 EMEA with a large number of nanoprecipitates, to achieve the synergy between high strength and large plasticity of the EMEA. It exhibits excellent comprehensive compressive mechanical properties, of which the compressive yield strength, fracture strength and fracture strain can reach 1154.5 MPa, 3178.4 MPa and 38.5%, respectively, superior to many conventional EHEAs (eutectic high-entropy alloys) and EMEAs, which can be attributed to the novel heterogeneous eutectic structure and the nanoprecipitates that result in additional strengthening without sacrificing plasticity. Highlights: A novel Fe20 Cr20 Ni30 Al30 eutectic medium-entropy alloy was designed and prepared. An excellent combination of yield strength (1154.5 MPa), fracture strength (3178.4 MPa) and strain (38.5%) has been achieved. The interface structures between the matrix and precipitate were analyzed. Strengthening mechanisms and phase formation of the EMEA were analyzed systematically.